Profile of Eyelid lesions: A Histopathological Study from a Tertiary Care Centre in Ajmer - Mishra, Neha; Porwal, Vandana; Khandelwal, Shweta; Rathi, Aparna; Porwal, Rakesh (Annals of Pathology and Laboratory Medicine, 2019)
Background: The literature is relatively sparse on the epidemiological and histopathological profile of eyelid lesions in Rajasthan. The present study aims to characterize the histopathological profile of both non-neoplastic and neoplastic eyelid lesions from a tertiary care centre in Ajmer, Rajasthan. Methods: A total of 55 lesions with histopathology diagnosis were included. Inflammatory non neoplastic lesions were excluded (15.38%). The lesions were categorized into three groups according to the origin: epidermal, adnexal tumors and ‘others’, including melanocytic, vascular lesions and others. Result: Total 55 biopsy specimens were evaluated of which, 44 cases (80%) were benign, 10 cases (18.18%) were malignant and single case (1.81%) was pre malignant. The age distribution varied from 2-81 years with mean age of 36.75 years. Benign lesions were seen more commonly in young boys of first decade and malignant lesions were more frequent in adult females. Most common benign tumors included epidermal cyst (31.81%) followed by hemangioma (18.18%), squamous papilloma (9.09%). Six cases of adnexal tumors (9.23%) were also noted. The most frequent malignant tumor included Basal cell carcinoma (81.81%). Only single case of sebaceous gland carcinoma was seen.